MENINGKATKAN SEMANGAT MENULIS DAN PUBLIKASI KARYA ILMIAH BAGI GURU SE-KECAMATAN SUHAID, KAPUAS HULU - Munawar Thoharudin; Fatkhan Amirul Huda; Tedi Suryadi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Scientific writing is now an important requirement for teachers in advancing their field of professional development. The general objective of this activity is to increase the enthusiasm of teachers in writing scientific papers and publish them in national journals as part of teacher professional development. Operationally, the objectives of this activity are: increasing knowledge of writing scientific papers for teachers in Suhaid District; improving the ability to write scientific papers for teachers; as well as the development of teachers in preparing research reports and articles until they are published in the mass media or accredited national scientific journals.The method used in this activity was performance and training in writing scientific papers. The expected outcome of this scientific paper writing workshop was that teachers could be motivated and understand how to write correct scientific papers. The results of the activities were proven by the participants’ sending the scientific papers by email to the instructor and the instructor reviewed the papers for revisions to achieve the output target of this activity.